Pengaruh Rasio C/N Campuran Feses Sapi Perah dan Daun Kirinyuh terhadap Kualitas POC (Pupuk Organik Cair) - Safari, Ari Abdulah; Hidayati, Yuli Astuti; Setiawati, Mieke Rochimi (Unpad Press, 2023)
This study aims to determine the effect of the C/N ratio of a mixture of dairy cow dung and kirinyuh leaves on the quality of extraction or Liquid Organic Fertilizer (POF). The treatment consisted of a mixture of dairy cow manure and kirinyuh leaves with different C/N, namely P1=16, P2=18, P3=20, P4=22. The treatment was decomposed for 14 days then extracted and incubated for 14 days. Observations included a decrease in C-organic content (%), total N-total (%), C/N ratio, P content (%), K content (%), the number of P-solvent bacteria (CFU/ml), Azosprillium (CFU/ ml) and Azotobacter (CFU/ml). The results showed that the effect of the C/N ratio only had a significant effect on the N parameter of composting where the best results were seen at a C/N ratio of 16. Meanwhile for the POC quality the parameters C, N and P had no significant effect, while for K parameter, total of P solubilizing bacteria, Azosprillium and Azotobacter had a significant effect. The highest levels of K and the total of Azotobacter were found at the initial C/N ratio of 16. Meanwhile, the highest total of P-solubilizing bacteria and the highest total of azosprillium were found at the initial C/N ratio of 22. Therefore an initial C/N ratio of 16 is recommended for composting dairy cow faeces. with kirnyuh leaves. While the extraction results are recommended to be focused on making biological fertilizers.